The Issues of Refugees in the Republic of Armenia - Abgaryan, Arusyan (Journal of Sociology: Bulletin of Yerevan University, 2018)
The article presents the definitions of the term “refugee”, presents the international convention and protocol, defining refugees, their rights and duties. Furthermore, the article discusses problems associated with the integration of refugees in their host countries.